Determination of the Polyphenol Composition of Raspberry Leaf Using LC-MS/MS - Hind Mesfer S. Alkhudaydi; Esther Njeri Muriuki; Jeremy P. E. Spencer (Molecules)
Background: Raspberry leaf (RL; Rubus idaeus) is a by-product of raspberry cultivation and has been proposed to be a rich source of micronutrients and potential bioactive components, including polyphenols. However, the precise chemical composition of the non-nutrient (poly)phenols in RL has not been as extensively studied. Objective: To evaluate the (poly)phenolic content of six RL samples from different geographical locations and to explore the impact of brewing duration on the levels of phenolic compounds available for absorption following consumption. Methods: A total of 52 polyphenolic constituents were investigated in the RL samples using Liquid Chromatography–Mass Spectrometry (LC-MS), and RL tea samples were analysed for ellagitannins, flavonoids, and phenolic acids. Tea samples were extracted using 80:20 (v/v) methanol/acidified water (0.1% formic acid) to maximise polyphenol recovery, with two sonication steps (30 and 25 min), followed by centrifugation, filtration, and storage at −18 °C. Extractions were performed in triplicate for comprehensive profiling. Additionally, raspberry leaf tea (2 g) was brewed in 200 mL of boiling water at various times (0.5–20 min) to simulate standard consumption practices; this was also performed in triplicate. This approach aimed to quantify polyphenols in the brew and identify optimal steeping times for maximum polyphenol release. Results: Raspberry leaf (RL) samples from six geographical sources were analysed, with 37 compounds identified in methanol and 37 in water out of the 52 targeted compounds, with only 7 compounds not detected in either methanol or water extracts. The analysis indicated that the total measured polyphenol content across the six samples from various sources ranged between 358.66 and 601.65 mg/100 g (p < 0.001). Ellagitannins were identified as the predominant polyphenolic compound in all RL samples, ranging from 155.27 to 394.22 mg/100 g. The phenolic acid and flavonoid concentrations in these samples exhibited a relatively narrow range, with the phenolic acids spanning from 38.87 to 119.03 mg/100 g and the flavonoids ranging from 125.03 to 156.73 mg/100 g. When brewing the tea, the 5 min extraction time was observed to yield the highest level of polyphenols (505.65 mg/100 g) (p< 0.001), which was significantly higher than that with shorter (409.84 mg/100g) and longer extraction times (429.28 mg/100 g). Notably, ellagic acid levels were highest at 5 min (380.29 mg/100 g), while phenolic acid peaked at 15 min (50.96 mg/100 g). The flavonoid content was shown to be highest at 4 min (82.58 mg/100 g). Conclusions: RL contains a relatively high level of polyphenols, particularly ellagic acid; thus, its consumption may contribute to the daily intake of these health-beneficial non-nutrient components.